Levels of Consumption, Satisfaction and Symptoms Relating to Two Types of Meals with Modified Texture in Dysphagic Subjects (P01-004-19). (13th June 2019) - Gregori, Dario; Sukkar, Samir Giuseppe; Diurni, Mario; Formenti, Laura; French, Megan; Carraro, Alice
Abstract: Objectives: This study investigated levels of consumption, satisfaction and symptoms between patients given one of two texture modified models, (i) smoothed dishes prepared traditionally in a kitchen (CF), and (ii) homogenized meals obtained from dehydrated and rehydrated instantaneous preparations by means of special equipment (OI). Methods: The study is an observational cohort of 30 patients aged between 41–81 years old with complex disability, intellectual disabilities, dysmorphism and medium-gravity dysphagia, and psychiatric, neurological, gastroenterological and endocrine comorbidities. Fifteen patients were fed the OI menu, and 15 were fed the CF menu. Follow-up was assessed at 2- and -4 months. Dissatisfaction scores were investigated using a modified Chernoff's scale based on three levels of smiles (the higher the score, the higher the dissatisfaction). Consumption of daily meals (breakfast, lunch, snack, dinner) and aquagel were recorded. Symptoms scoring (0–14) has been built by counting the occurrence of symptoms on a weekly basis (0 = never/absences of symptoms; 1 = one symptom per week; 3 = one to two symptoms per week; 10 = one to two symptoms per day; 14 = always). Statistical analysis was performed using R. Results: Over the entire follow-up period (4 months), mean levels of consumption are significantly higher in the OI group in comparison to the CF group (p-values < 0.001), and dissatisfaction significantly lower (p-values < 0.001). This is also evident when analysis is stratified by meal occasion. Analysis of trends over time identified a clear tendency toward improved consumption and greater satisfaction. Significantly lower symptom scores are always evident in the OI group in comparison to the CF group. Conclusions: Analysis of levels of consumption, dissatisfaction scoring and symptoms scoring shows that patients receiving the modified homogenized instantaneous meal (OI) have overall higher consumption levels, greater satisfaction, and less symptoms than patients receiving traditionally prepared smoothed dishes (CF). Funding Sources: Zeta Research S.r.l.